The Palestinian diaspora : formation of identities and politics of homeland - Schulz, Helena Lindholm (Global diasporas (Routledge (Firm)), 2003)
From the refugee camps of the Lebanon to the relative prosperity of life in the USA, the Palestinian diaspora has been dispersed across the world. In this pioneering study, Helena Lindholm Schulz examines the ways in which Palestinian identity has been formed in the diaspora through constant longing for a homeland lost. In so doing, the author advances the debate on the relationship between diaspora and the creation of national identity as well as on nationalist politics tied to a particular territory. But The Palestinian Diasporaalso sheds light on the possibilities opened up by a transnational existence, the possibility of new, less territorialized identities, even in a diaspora as bound to the idea of an idealized homeland as the Palestinian. Members of the diaspora form new lives in new settings and the idea of homeland becomes one important, but not the only, source of identity. Ultimately though, Schulz argues, the strong attachment to Palestine makes the diaspora crucial in any understandings of how to formulate a viable strategy for peace between Israelis and Palestinians.